On $ψ$ gs-Functions in Bitopological Spaces (European Journal of Pure and Applied Mathematics, 2024)
A subset $A$ of a bitopological space $(X,\tau_1,\tau_2)$ is called  \emph{$(i,j)$-$\psi$gs-closed} set if\\ $(i,j)\text{-}\psi cl(A)\subseteq U$ whenever $A\subseteq U$, $U$ is $(i,j)$-semi-open in $(X,\tau_1,\tau_2)$. In this work, the propertiesof this set are considered to investigate the concepts of $\psi gs$-functions in bitopological spaces. Specifically, this study establishes some properties and provide characterizations of $\psi gs$-open and  $\psi gs$-closed functions, $\psi gs$-continuous functions, and  $\psi gs$-irresolute functions in bitopological spaces.
Keywords: bitopological spaces; $ψ$gs-closed set; $ψ gs$-open function; $ψ gs$-closed function; $ψ gs$-continuous function; $ψ gs$-irresolute function